O fenômeno Vlog no Youtube : análise de conteúdo de Vloggers brasileiros de sucesso - Dornelles, Juliano Paz (2014)
We develop in this Master Dissertation a content analysis of four Brazilians wellsucceeded vloggers: Felipe Neto, Acid Girl, PC Siqueira and Silvio Matos. The social role of the so-called vloggers became evident among us during the last decade. Their videos become, in some cases, popular, being, in this case, shared and commented in everyday conversation in and outside the internet. We aim here to understand the character of the narratives and interventions of the mentioned vloggers, stressing the autobiographical marks they inscribe in this phenomenon. For this, we employ a hybrid methodology. Their YouTube videos are used as documental source, while the ideas of some researchers, as Paula Sibília, are invoked as theoretical references to conduct their examination. In sum, we stress the common features and formulas of their messages, specially the way their creators employ a sarcastic humor language to develop a critical commentary about our common circumstances.